Telework During Pandemic: Comparing Readiness between Local and Central Government Employees - Muhamad Azami Nasri; Muhammad Nurdin Alamsyah; Doni Ramadhan; Reza Fathurrahman (Indonesian Association for Public Administration (IAPA), 2020)
Employing Holt, et al.’s (2007) Readiness for Change Theory, this study investigates the readiness level among the local and central government employees to embrace the unanticipated Telework policy during the COVID-19 pandemic. For this purpose, individual perceptions of 383 respondents (237 central and 146 local government employees) were analyzed using the Mann-Whitney test. The statistical results reveal that the respondents who represent central government employees show significantly higher readiness level than their colleagues from the local regions. Further analysis at the dimensional level provides further explanation for this: It is evident that the central civil servant respondents show their superiority over local civil servant respondents on the three aspects, namely the level of understanding about the urgency of changing the way of working to telework, confidence in learning new skills to support telework, and awareness of the potential benefits of telework for themselves respectively. Interestingly, there is no significant difference between the two groups in terms of managerial support.